The Role of Government Public Relations in Digital Media in Building a Positive Image of the Central Sulawesi Provincial Government - Intje Yusuf; Muhammad Khairil; Sitti Murni Kaddi (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to analyze the role of government public relations in utilizing digital media to build a positive image of the Provincial Government of Central Sulawesi. In the digital era, government public relations hold a strategic responsibility to deliver accurate, transparent, and relevant information to the public. However, various obstacles such as limited human resource capacity, the spread of misinformation, and digital infrastructure disparities often reduce the effectiveness of communication. This study employs a qualitative approach with a case study method, involving in-depth interviews, digital media content analysis, and observations of public relations practices in the region. The findings reveal that the use of digital media by the public relations of the Provincial Government of Central Sulawesi still faces challenges in terms of consistency in information delivery and issue management on social media. Nevertheless, there is significant potential to improve the government’s image through better-planned, collaborative, and inclusive digital communication strategies. This study provides recommendations to enhance human resource capacity, expand digital infrastructure reach, and strengthen response mechanisms to negative information on social media. These efforts are expected to enable public relations to effectively build trust and foster a harmonious relationship between the government and the public